PENGARUH KUALITAS PELAYANAN, LOKASI, DAN TARIF TERHADAP KEPUASAN PASIEN RAWAT INAP RUMAH SAKIT LESTARI RAHARJA KOTA MAGELANG (Studi Kasus Pada Pasien Rawat Inap Non Asuransi) - Difa Nurulia Safitri; Wahyu Hidayat; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2015)
Nowadays, people has been aware about the importance of health. Public awareness about the importance of health is an opportunity for health sevice especially hospital. Therefore, many hospitals are competing to provide satisfaction for its customers. There are several factors that affect patient satisfaction such as service quality, location, and hospital rate. Based on the existing problems in this research is the result of pre-survey of 30 respondents which indicate patient dissatisfaction. This research purpose to find out positive and significant influence of service quality, location, and hospital rate on hospitalized patient satisfaction at Lestari Raharja Hospital Magelang. This research included in explanatory. Taked 88 respondents as sample with proportionate stratified random sampling method. Collecting data used questionnaire and interview. Hypotheses tested by crosstab, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, t test, and F test. The result of this research show that service quality, location, and hospital rate are proved have positive and significant affect in partially and simultaneously on Patient Satisfaction.